PHARMACEUTICAL STANDARDIZATION OF RAKTAPACHAK VATI (TABLET) - A POLYHERBAL FORMULATION - Pawar, Vijay G.; Ramteke, Vinod M.; Deshpande, Sarang; Gadkari, Kishor; Pable, Tarun (International Journal of Ayurveda and Pharma Research, 2017)
In Ancient Ayurvedic texts, there are many formulation, some of them are herbal, mineral and herbo-mineral in origin. These formulations are effective in many diseases depending upon their qualities and properties. In Charak Samhita, Uttarsthana, Acharya Charak mentioned Pachak Yoga in the Treatment of Vishamjwara. Raktapachak yoga which is useful in the treatment of Raktagat jwar(satat jwar). Many of the Ayurvedic practioners prescribe Raktapachak Yoga in various dosage forms like Kashaya (Decoction), Churna (Powder) etc as per their convenience. Dosage form for administration plays an important role in the packaging, action and delivery of the particular drug on a specific system. Tablets are easy to prepare, packaging, transportation and administration to the patients Hence tablet form is the most accepted dosage form amongst all. This formulation is transformed to the tablet form by using modern equipments and analytical techniques. An effort is made to validate the pharmaceutical and analytical procedures to maintain the quality of product and to avoid batch to batch variation. Pharmacopoeial standards are set for this Ayurvedic formulation in tablet form. All the three samples were prepared by this method shows identical characteristics and analytical parameters do not show much significant difference. The set parameters may be used for the further pharmaceutical preparations.